Cartap and carbofuran induced alterations in serum lipid profile of Wistar rats - Rai, Devendra K. (Springer-Verlag, 2009)
Wistar rats of 6–8 weeks in age weighing between 120–150 g were exposed to the fixed doses of each of the carbamate pesticides such as cartap (50% LD(50)) and carbofuran (50% LD(50)) as well as a combination of these two with 25% LD(50) of each for one week. The effect of treatments was studied in terms of serum lipid parameters such as high-density lipoprotein, total cholesterol, triglyceride, low-density lipoprotein and very low-density lipoprotein. Treatment with individual doses of carbofuran (50% LD(50)) and cartap (50 % LD(50)) caused significant alterations in the levels of serum lipid parameters. The pesticides treatment resulted in marked decrease in the level of serum high-density lipoprotein where as that of other lipids got significantly elevated. Further, the rats exhibited relatively higher impact of pesticides when treated with the compounds in combination (25 % LD(50) of each). The results indicated that these compounds when used together may exert enhanced effect on the levels of serum lipids in rat.